Theridion echinatum Gao & Li, 2014, a junior synonym of Theridion zonulatum Thorell, 1890 (Araneae, Theridiidae) with comments on its web architecture - Sankaran, Pradeep M.; Malamel, Jobi J.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2015)
The spider genus Theridion was established by Walckenaer in 1805 with Theridion pictum (Walckenaer, 1802) as the type species. It is the most ‘species rich’ theridiid genus comprising 584 described species and 6 subspecies (World Spider Catalog 2015). Theridion zonulatum Thorell, 1890, ‘the zebra theridiid spider’, which is known only by the female, was described from Sumatra. Gao & Li (2014) described Theridion echinatum from the Yunnan Province in China based only on male specimens. During our surveys of Indian spiders, we came across a matching-pair of male and female theridiid spiders from the Kerala region in India. Our female spiders appeared to belong to T. zonulatum, while male spiders shared the features of T. echinatum. This led us to the conclusion that both T. zonulatum and T. echinatum are conspecific. In the present paper, we synonymise T. echinatum with T. zonulatum. The web architecture of T. zonulatum is also described.